KINEMATIC ANALYSIS OF CLASSICAL SKIING TECHNIQUE IN SPRINT FOR YOUNG AND ADULT ATHLETES - Novikova N.B. ,; Belyova A.N. ,; Ivanova I.G. ,; Kotelevskaya N.B. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the features of the kinematics of the alternating two-step course of young athletes at a sprint distance and to compare the angular characteristics of the main phases of the course with the indicators of the strongest athletes in the world. Methods and structure of the study. A biomechanical analysis of the classic skiing technique for men and women in the prologesprint at the stage of the World Cup and boys and girls aged 14-16 at the distance of the Russian Championship was performed. The angular characteristics of the key moments of the ski course are determined and the main differences in the technique of young and adult athletes of various qualifications are revealed. Results and conclusions. The analysis of the kinematic characteristics shows that the technique of sprinting uphill skiers and skiers of different ages and levels of fitness has significant differences. Men and boys more often use the modern running version of the alternating two-step move, women, although they run uphill without a rolling phase, as a rule, demonstrate the traditional version without active bending of the fly leg. Young men use various variants of uphill sprinting, including the modern way of movement "Klaebostyle", but the average values of the angular characteristics in the lunge, ski stop and sit-down positions indicate the existing reserves for improving the technique.